Understanding the Experiences of Mothers with Academic Socialization in South Korea: A Phenomenological Approach. - Chun, Heejung; Son, Hoyang; Ham, Kyong Ae (Journal of Child & Family Studies, 2023)
We explored academic socialization experiences of nine mothers in South Korea. Academic socialization has been defined as parents' practices that transfer their educational expectations, values, and aspirations to their children (Hill, 2001). Adopting Giorgi's phenomenological research method (1997), we interviewed nine mothers who had recently prepared their children to get into college. The interviews were focused on the ways in which they intervened in the academic process when their children were in high school. The data analysis proceeded along the four steps suggested by Giorgi (1997). The analysis resulted in the 12 constituents, which are the themes underlying the essential structure of the academic socialization experiences. The findings showed that during the academic socialization process, all participating mothers set high academic standards for their children. The mothers actively engaged in supporting their children through shadow education (i.e., supplementary private education) to strengthen their academic competitiveness. Further, the mothers found themselves competing with other mothers regarding the academic achievement of their children. The mothers rather than their children took initiatives for decision makings of academic matters. Some of their practices were noticed to have compromised the autonomy of their children. The mothers appeared to fulfill their needs that prove their self-worth by raising their children to be competent. The significance and implications of these results were discussed. Highlights: Mothers' practices of academic socialization in South Korea unfold under the cultural and societal contexts of educational zeal, competitive educational climate, and shadow education dependency. During the academic socialization process, mothers take initiatives to improve the academic rankings of their children and compromise their autonomy. Mothers frequently engage in competitions with other mothers regarding the academic performance of their children. Mothers believe that the essence of their role is providing best shadow education programs or tutors.